The Role of FtsH Complexes in the Response to Abiotic Stress in Cyanobacteria - Krynická, Vendula; Komenda, Josef (Plant & cell physiology, 2024)
FtsH proteases (FtsHs) belong to intramembrane ATP-dependent metalloproteases which are widely distributed in eubacteria, mitochondria and chloroplasts. The best-studied roles of FtsH in Escherichia coli include quality control of membrane proteins, regulation of response to heat shock, superoxide stress and viral infection, and control of lipopolysaccharide biosynthesis. While heterotrophic bacteria mostly contain a single indispensable FtsH complex, photosynthetic cyanobacteria usually contain three FtsH complexes: two heterocomplexes and one homocomplex. The essential cytoplasmic FtsH1/3 most probably fulfills a role similar to other bacterial FtsHs, whereas the thylakoid FtsH2/3 heterocomplex and FtsH4 homocomplex appear to maintain the photosynthetic apparatus of cyanobacteria and optimize its functionality. Moreover, recent studies suggest the involvement of all FtsH proteases in a complex response to nutrient stresses. In this review, we aim to comprehensively evaluate the functions of the cyanobacterial FtsHs specifically under stress conditions with emphasis on nutrient deficiency and high irradiance. We also point to various unresolved issues concerning FtsH functions, which deserve further attention.
Keywords: bakteriální proteiny; Stress, Physiological; ATP-Dependent Proteases; Nutrient stress; proteasy závislé na ATP; FtsH; Photosystem; fyziologický stres; Cyanobacteria; Bacterial Proteins; Photodamage; sinice